2021
DOI: 10.3386/w29015
|View full text |Cite
|
Sign up to set email alerts
|

Entrepôt: Hubs, Scale, and Trade Costs

Abstract: Entrepôts are hubs that facilitate trade between multiple origins and destinations. We study these entrepôts, the network they form, and their impact on international trade. We document that the trade network is a hub-and-spoke system, where 80% of trade is shipped indirectly-nearly all via entrepôts. We estimate indirect-shipping consistent trade costs using a model where shipments can be sent indirectly through an endogenous transport network and develop a geography-based instrument to estimate economies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…First, the markup over the marginal cost of transportation increases in market power: According to it is lower on thick routes with more carriers and greater traffic. Second, larger traffic prompts carriers to use larger vessels, which minimizes the average cost of transportation (Asturias, 2020;Ganapati et al, 2020). Both effects work in the same direction lowering the observed freight rates on thicker routes with larger traffic.…”
Section: Contract Versus Spot Marketsmentioning
confidence: 98%
See 3 more Smart Citations
“…First, the markup over the marginal cost of transportation increases in market power: According to it is lower on thick routes with more carriers and greater traffic. Second, larger traffic prompts carriers to use larger vessels, which minimizes the average cost of transportation (Asturias, 2020;Ganapati et al, 2020). Both effects work in the same direction lowering the observed freight rates on thicker routes with larger traffic.…”
Section: Contract Versus Spot Marketsmentioning
confidence: 98%
“…The network structure of the containerized shipping was explored in detail by Heiland et al (2019) and Ganapati et al (2020). The latter also showed that a handful of ports play a disproportionately significant role: 25 Stylized Fact 18.…”
Section: Contract Versus Spot Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…A frequently mentioned motive for using merchants, especially when they are located in entrepôts, is transport cost savings. Authors such as Andriamananjara et al (2004), Wang and Wang (2011), Kojaku et al (2019) and Ganapati et al (2020) discuss how rapid change in transportation technology during recent decades has strengthened economies of scale in transportation (in addition to causing a vast reduction in shipment costs and contributing to a stark globalization of value chains). This, in turn, has enhanced a hub-and-spoke system in international trade, where most products traded over long distances are first transported by large container ships to certain hub countries with favorable geographic locations, strong histories of maritime trade and large seaports with well-developed infrastructure.…”
Section: Saving Transport Costs and Evading Tariffsmentioning
confidence: 99%